Comparison of the effect of typical patterns on friction and wear properties of chromium alloy prepared by laser surface texturing. (October 2018) - Lu, Libin; Zhang, Zhen; Guan, Yingchun; Zheng, Hongyu
Graphical abstract: The CoF of different specimens with different parameters: (a) micro-dimples; (b) micro-grooves; (c) micro-grids; (d) average CoF. Highlights: It is analyzed three typical patterns at metallic surface induced by laser texturing. The maximum wear rate reduction of 57% is achieved at micro-grids pattern surface. The friction coefficients of all laser-textured surfaces are lower than those of as-received surfaces. The FEA results show that surface texturing can avoid stress concentration during sliding processes. Abstract: Chromium alloy has been widely employed in industry due to high strength and corrosion resistance. However, poor tribological performance directly affect the lifetime of chromium-based components. In order to improve surface properties of chromium alloy, we investigate the effect of typical patterns including micro-dimples, micro-grooves and micro-grids on their friction and wear behaviors generated by laser surface texturing. Experimental results show that laser-textured surfaces significantly reduce the wear volume up to 57%, especially for surface patterns with micro-grids. The enhanced wear performance is mainly caused by the increased microhardness in local quenched zones, the capability of trapping wear debris and uniform stress distribution during friction sliding process.